2020
DOI: 10.3389/fneur.2020.00292
|View full text |Cite
|
Sign up to set email alerts
|

Nonmotor Symptoms Affect Sleep Quality in Early-Stage Parkinson's Disease Patients With or Without Cognitive Dysfunction

Abstract: Purpose: Parkinson's disease (PD) patients frequently present with sleep disorders. This study was designed to assess the impact of nonmotor symptoms (NMSs) on sleep quality in early-stage PD patients with and without cognitive dysfunction. Materials and Methods:A sample of 389 early-stage PD patients (modified Hoehn and Yahr score ≤2.5, duration ≤5 years) was recruited for the present study. The Non-Motor Symptoms Questionnaire (NMS-Quest) was used to screen for global NMSs. Depressive symptoms were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…25 Furthermore, the presence of comorbidities and non-PD medications, which could serve as cofounders, are not described in many studies. For example, some studies suggest that nocturnal motor symptoms (rigidity, reemergence of tremor in light sleep, PLMS), 84 pain, 59 nocturia, 85 and hallucinations 40,86,87 can contribute to sleep changes, although such symptoms are not always systematically evaluated. Finally, the majority of these studies describe group-level differences, which limits inferences on whether the identified spectral changes index disease progression or represent dynamic withinsubject biomarkers.…”
Section: Summary Of Psg-based Studiesmentioning
confidence: 99%
“…25 Furthermore, the presence of comorbidities and non-PD medications, which could serve as cofounders, are not described in many studies. For example, some studies suggest that nocturnal motor symptoms (rigidity, reemergence of tremor in light sleep, PLMS), 84 pain, 59 nocturia, 85 and hallucinations 40,86,87 can contribute to sleep changes, although such symptoms are not always systematically evaluated. Finally, the majority of these studies describe group-level differences, which limits inferences on whether the identified spectral changes index disease progression or represent dynamic withinsubject biomarkers.…”
Section: Summary Of Psg-based Studiesmentioning
confidence: 99%
“…Total sleep time (TST), wake time after sleep onset (WASO), sleep efficiency (SE), sleep latency (SL), and REM sleep latency (RSL) were recorded. Sleep disorders were determined for WASO ≥ 60 min, SL ≥ 30 min, and SE < 85% on the PSG as well as PDSS < 105 ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Better cognition is associated with better sleep quality, and may as well predict it. NMS hallucinations/delusions score was the most crucial determinant condition for sleep disorders in the patients with CI; among those without CI, NMS such as anxiety and medication were associated with sleep disorders (62). One metaanalysis showed a big influence of sleep (or, rather, lack thereof) on global cognitive function, long-term verbal recall, long-term verbal recognition, shifting, updating and fluent reasoning.…”
Section: Apathymentioning
confidence: 98%